The Impact of Viscose Rayon Fiber Exposure on Lung Function - Khairani, Muhammad; Esha, Indi; Suyanto, Suyanto (Jurnal Respirasi, 2025)
Viscose rayon fiber is a semi-synthetic material derived from regenerated cellulose. The cellulose used to make viscose rayon is extracted from natural sources, resulting in fibers that are physically similar to cotton and have characteristics such as softness and high absorbency. The viscose manufacturing process involves chemical modification of cellulose using carbon disulfide (CS2), which is dangerous if exposed to humans. Carbon disulfide residues, along with endotoxin biological agents present on rayon fibers, can be inhaled into the respiratory tract. This causes oxidative protein damage, which then activates the oxidative stress response. This response ultimately results in the release of oxidants that induce inflammatory mediators, triggering acute or chronic inflammatory reactions in the airways and alveoli, resulting in decreased lung function. A systematic approach is essential for gathering and interpreting relevant data. This approach can be organized into seven steps to diagnose occupational lung diseases. The use of personal protective equipment (PPE) represents the final but most important defense. Recommended PPE includes respirator masks with suitable particle filters, protective eyewear to prevent eye irritation, chemical-resistant gloves to protect the skin from direct contact, and full-body work clothing.